La fabrique d’un paysage - Jean-Marc Pinet (Projets de Paysage)
Nothing natural in a landscape, but a cultural construction, according here to three ways in a same man. As a highlander, a geographer and a painter, Franz Schrader selects, represents and paints a mountainous landscape in the French Pyrenees. The result of his three cross gazes is a picture in keeping with its time, at a two centuries turning.